Nanochemistry of molybdenum dichalkogenides and tungsten dichalkogenides: new potentialities of designing nanomaterials - Kulikov, L. M.; Kenig, N. B.; Akselrud, L. G.; Davydov, V. N. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2007)
Some results of regular investigations in the field of nanochemistry of layered d-Transitive Metals Dichalcogenides: synthesis, structural, structural-sensitive physical and physical-chemical properties of nanostructures, intercalated nanosystems on their basis are submitted.